Menikahi Perempuan Hamil Karena Zina dan Kedudukan Anak Zina Perspektif Fikih dan Hukum Positif - Jinawar Al-Yamani, Adnan (Wasathiyyah, 2023)
Zina is considered a major sin in Islam, carrying significant legal, moral, and social implications for the perpetrators and society. This study aims to analyze the legal framework surrounding the marriage of pregnant women due to zina and the status of children born out of zina from the perspectives of Islamic jurisprudence (fiqh) and Indonesia's positive law. The research employs a qualitative approach through literature studies on scholarly opinions from various Islamic schools of thought and analysis of national legal provisions, such as the Marriage Law and the Compilation of Islamic Law (KHI). The findings reveal differences among Islamic scholars regarding the permissibility of marrying pregnant women due to zina. Some scholars allow it under specific conditions, such as observing iddah and repentance, while others prohibit it until childbirth. In positive law, children born out of zina are only recognized as having a civil relationship with their mother, whereas acknowledgment of their father requires legal proceedings. The lack of alignment between Islamic law and positive law presents challenges in harmonizing religious values with modern legal needs. This study emphasizes the importance of a holistic approach in addressing the legal issues surrounding the marriage of pregnant women due to zina and the status of children born out of zina. Harmonizing sharia principles with national legal regulations is essential to provide equitable and comprehensive solutions while safeguarding the rights of all parties involved. This research aims to serve as a reference for the development of legal policies that are more relevant and adaptive to social changes.